2008
DOI: 10.7205/milmed.173.9.913
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ametropia among Military Beneficiaries

Abstract: In addition to active duty military members and their dependents, retired military members and the members of their immediate families are eligible for eye care in military medical treatment facilities. We recorded refractive errors, age, sex, and race for 4,595 individual beneficiaries visiting optometry clinics at two U.S. Air Force medical treatment facilities during 2005 to 2006. Evaluation revealed most patients requiring optical correction were myopic, or near-sighted, and there was an increase in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Quek et al (2004) found a high prevalence of myopia in a Singaporean sample of students from 15 to 19 years old, and Saw et al (2007) found that myopia was associated with better academic performance. Other authors have also found variations in the prevalence of myopia across cultures (Collins & Berg, 2008;Holden et al, 2014;Lam, Lam, Cheng, & Chan, 2012;Logan, Shah, Rudnicka, Gilmartin, & Owen, 2011;Plainis et al, 2009;Saw, 2003;Saw, Katz, Schein, Chew, & Chan, 1996). Quek et al (2004) found the overall prevalence of myopia was 73.9% with moderate myopia (Ϫ1.00 diopters) at 56.1%.…”
Section: Cross-cultural Evidencementioning
confidence: 89%
“…Quek et al (2004) found a high prevalence of myopia in a Singaporean sample of students from 15 to 19 years old, and Saw et al (2007) found that myopia was associated with better academic performance. Other authors have also found variations in the prevalence of myopia across cultures (Collins & Berg, 2008;Holden et al, 2014;Lam, Lam, Cheng, & Chan, 2012;Logan, Shah, Rudnicka, Gilmartin, & Owen, 2011;Plainis et al, 2009;Saw, 2003;Saw, Katz, Schein, Chew, & Chan, 1996). Quek et al (2004) found the overall prevalence of myopia was 73.9% with moderate myopia (Ϫ1.00 diopters) at 56.1%.…”
Section: Cross-cultural Evidencementioning
confidence: 89%
“…Additionally, sex estimation based on the design and style of the eyewear frame is not practical due to unisex products in several manufacturers. The uniqueness of specific refractive errors serves as potential tool for individualization but not in sex estimation [41].…”
Section: Discussionmentioning
confidence: 99%
“…In Ugandan soldiers, a higher prevalence rate for myopia was reported (33). Collins and Berg found that the prevalence of myopia is three times higher than that of hyperopia among military beneficiaries in the United States (34). Moreover, the prevalence rate of myopia and hyperopia among refractive errors was 75.8% and 11.7%, respectively, in the study of military service in Poland (35).…”
Section: Introductionmentioning
confidence: 96%
“…ulation. Different evaluations on military individuals and army arrival volunteers have shown that myopia is more frequent than hyperopia in different parts of the world (31)(32)(33)(34)(35). The prevalence of hyperopia (19.6%) was less than that of myopia (37.7%) in Swedish military recruits (31).…”
Section: Introductionmentioning
confidence: 99%